Comparative Analysis of the Influence of Powder Factor and Energy Factor in Blast Design - ADESIDA, Patrick Adeniyi (ABUAD Journal of Engineering and Applied Sciences, 2024)
Blast design is critical to blasting operations’ cost efficiency and productivity. A key factor in estimating the cost efficiency of a blast design is the powder factor, which measures the volume of rocks fragmented by a unit explosive. Debate on charge density’s influence on blast productivity has led to assumptions that the energy generated by explosives should be considered rather than the mass. Thus, this study aims to compare the influence of energy and powder factors on blast design and determine the most appropriate approach to blast planning. Data obtained from existing quarries were the burden, drilled-hole diameter, spacing, drilled-hole depth, mass of explosives, stemming, number of holes blasted, and the uniaxial compressive strength. These data were used to estimate the power and energy factors. Multivariable regression analysis was used to predict burden using drilled-hole diameter, uniaxial compressive strength energy factor, and powder factor. The results show that the burden prediction model using energy factor has a coefficient of determinants (R2) value of 0.8741, a standard error of 0.24, and a significance factor of 3.47E-09., while the prediction involving powder factor value is 0.8781, the standard error is 0.24, and the significance factor is 2.52E-09. The study concluded that the powder and energy factors influence blast design similarly. However, in this study, the use of powder factor is recommended because of its ease of estimation.